When Tradition Meets Modernity: The Adaptation of Bajau Community in Malaysia Amidst Sociocultural Transformation - Zainuddin, Mohd. Fadzil (Journal of Contemporary Rituals and Traditions, 2023)
This research aims to analyze how the Bajau community in Kulambai Village, Kota Belud, Sabah, Malaysia, adapts their traditional practices in response to modernization. Modernization has brought significant changes in various aspects of life, including local culture and traditions. The Bajau community, having lived with local wisdom and distinctive traditions, now faces significant pressure to integrate with the ever-evolving modern world. This study utilizes a qualitative approach, collecting data through in-depth interviews with members of the Bajau community in Kulambai Village. Participatory observation is also conducted to understand how traditional practices interact with modern elements in daily life. The collected data are then analyzed to identify patterns and key findings related to traditional adaptation in the face of modernization. The research results indicate that the Bajau community in Kulambai Village is experiencing changes in their traditional practices in response to modernization. They face a dilemma between preserving their cultural identity and adapting to the social and economic changes brought by modernization. Factors such as education, urbanization, and media influence also affect this adaptation process. Resource limitations and challenges in maintaining local wisdom pose obstacles for the Bajau community. Nevertheless, efforts to preserve traditions and cultural values are continually made by some Bajau community groups. This research provides a deeper understanding of how the Bajau community in Kulambai Village adapts their traditional practices in the face of modernization. The results can make a significant contribution to efforts to preserve local culture and traditions amidst rapid social change. Recommendations for further research include expanding the scope of the study to Bajau communities in other regions and deepening the analysis of modernization's impact on their cultural aspects.